Efek Ekstrak Etanol Biji Pinang Muda (Areca Catechu L.) Terhadap Aktifitas Sistem Saraf Pusat Mencit Putih - Arifin, Helmi; Riyono, Heppy; Elka, Elka (Fakultas Farmasi Universitas Andalas, 2010)
The central nervous system stimulant activity of the ethanol extract of young areca nut (Areca catechu L.) has been studied on mice. The observation was done by assessing the indurance, motor activity, curiousity, sleeping induced time and sleeping time in many variable of doses. Results showed that the ethanolic extract of 500 mg/ Kg bodyweight dose showed significant effect (P<0,05).